The impact of presurgical orthopedics appliances (PSOAs) in bilateral cleft patients - Yeap, Saliza Ainudin (2017)
Introduction: Acceptable maxillary growth in bilateral cleft lip and palate (BCLP) is difficult to achieve. Presurgical orthopaedic treatment aims at reduction of cleft size by guiding growth and functional rehabilitation. The objectives of this study were to evaluate the impact of Presurgical Orthopaedic Appliances (PSOA) on facial growth in BCLP. Methods: Subjects were patients who were treated in Hospital Universiti Sains, Malaysia, and Hospital Raja Perempuan Zainab II. Ages ranged 7 – 21 years of age with nonsyndromic cleft and no associated anomalies. A lateral cephalogram was taken and analyzed from it. Results: The study sample comprised of 52 BCLP patients (26 had PSOA and 26 did not have PSOA). Among these patients, those who had PSOA had PNS-ANS (3.69 mm; P = 0.04) and Co-A (8.38; P=0.04) compared to those who did not have PSOA. Conclusion: The usage of PSOA gives a shorter maxillary length in the facial growth of bilateral cleft patients.